BIOCHEMICAL PROCESSES AND STRUCTURES IN KIDNEY FUNCTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The kidneys play a critical role in maintaining bodily homeostasis by carrying out various essential functions, such as filtering the blood, regulating water-electrolyte balance, acid-base homeostasis, and excretion of waste products. These functions are supported by biochemical reactions that occur within the kidneys and ensure their basic physiological processes, including homeostasis, endocrine activity, and metabolic processes.